Determinant Factors of Cognitive Frailty in Elderly Patients - Santoso, Valencia; Rensa, Rensa (UI Scholars Hub, 2022)
Introduction. Physical frailty and cognitive impairment have a strong relationship and there are differences in factors associated with cognitive frailty. This research aimed to determine the prevalence of cognitive frailty and identify factors associated with cognitive frailty in the elderly population in hospital polyclinic. Methods. A cross-sectional study with secondary data on patients aged ≥60 years in the Internal Medicine Polyclinic of Atma Jaya Hospital, Jakarta, from May 2020 to May 2021. The independent variables of this study were age, cardiovascular disease, type 2 diabetes mellitus, dyslipidemia, risk of malnutrition, risk of depression, and functional status. The alternative criteria by Won et al. were used to classify cognitive frailt. Bivariate analysis (chi-square test) and multivariate analysis (logistic regression) were performed using SPSS program. Results. There were 343 subjects with a median age of 66 years, 35% had cardiovascular disease, 5.2% had a high risk of malnutrition, 9.3% had depressive symptoms, 20.4% had a low functional status (ADL-Barthel index), 55.7% were diagnosed with type 2 diabetes mellitus, and 36.4% were diagnosed with dyslipidemia. The prevalence of subjects with cognitive frailty is 1.2% and 98.8% without cognitive frailty. The determinant factor of cognitive frailty is the presence of cardiovascular disease [OR 10.17 (95% CI 0.97-106.54); p=0.05]. Conclusions. Prevalence of cognitive frailty in elderly outpatients is 1.2%. The determinant factor of cognitive frailty is cardiovascular disease.